Determination Of Generation Z's Intention In Using E-Wallet For Payment Transactions - Saputra, Irwan Adimas Ganda; Yusuf, Achmad; Hakim, Luqman; Rohayati, Suci (E-Jurnal Akuntansi; Vol 33 No 1 (2023)DO - 10.24843/EJA.2023.v33.i01.p06, 2023)
This study aims to analyze the factors that influence Generation Z's intention to use e-wallets as a means of payment transactions. Data was collected by distributing questionnaires, analyzed using SEM PLS. The sampling collection technique used purposive sampling and collected a balance of 214 respondents. The results of the analysis show that usefull has no effect on attitude towards use, financial literacy has a significant influence on behavioral intention to use and attitude towards use as an intervening variable has a role to mediate between digital literacy, easy to behavioral intention to use but has no role to mediate relationship between financial literacy and euseful to behavioral intention to use. These results can provide information regarding the characteristics and behavior patterns of generation Z towards the existence of e-wallets and provide information to e-wallet application developers in developing the features and benefits of services available on e-wallet applications. Keywords : Behavioral Intention To Use; E-Wallet; Generation Z